Puppet goat newsreader covers food security, grain prices - Aicha Boro, Chloé (Technical Centre for Agricultural and Rural Cooperation, 2006)
The biggest star of Burkinese television is a puppet goat that interviews agricultural experts and reads out the latest prices for cattle and grains